Maternal and fetal outcomes following the trial of vaginal delivery and elective repeat caesarean section in term pregnancy with one previous lower segment caesarean section in Dr. Baba Saheb Ambedkar Hospital: a prospective controlled study - Mahajan, Puneeta; Gupta, Vinita; Agrawal, Neha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Before 1970s, the phrase “once a caesarean, always a caesarean” was a common norm. Now this phrase has been changed to “once a caesarean, always an institutional delivery”. Methods: This prospective controlled study was carried out in department of obstetrics and gynaecology, Dr. Baba Saheb Ambedkar Medical College and Hospital, Rohini, Delhi for a period of 7 months (October 19 to April 2020) and included 200 gravid women with previous one lower segment caesarean section (LSCS). The ethical committee approval for the study was taken. Results: The success rate of trial of labour after caesarean (TOLAC) in our study was 67%. It was concluded from this study that the percentage of woman having complications were maximum in failed TOLAC patients which was 69.70% followed by patients undergoing elective repeat caesarean delivery (ERCD) which was 59% followed by women having successful VBAC which was 8.96%. The percentage of neonate having complications were maximum in neonate of failed TOLAC patients which was 27.27% followed by neonate of patients undergoing ERCD which was 21% followed by neonate of women having successful VBAC which was 5.97%. Conclusions: TOLAC for a second delivery is a much-needed feasible option in developing countries to reduce the cost and morbidities of repeat caesarean deliveries.